Insect nicotinic acetylcholine receptor gene families: from genetic model organism to vector, pest and beneficial species. - Jones, A; Brown, L; Sattelle, D (2007)
Nicotinic acetylcholine receptors (nAChRs) mediate fast synaptic transmission in the insect nervous system and are targets of a major group of insecticides, the neonicotinoids. Analyses of genome sequences have shown that nAChR gene families remain compact in diverse insect species, when compared to their mammalian counterparts. Thus, Drosophila melanogaster and Anopheles gambiae each possess 10 nAChR genes while Apis mellifera has 11. Although these are among the smallest nAChR gene families known, receptor diversity can be considerably increased by alternative splicing and mRNA A-to-I editing, thereby generating species-specific subunit isoforms. In addition, each insect possesses at least one highly divergent nAChR subunit. Species-specific subunit diversification may offer promising targets for future rational design of insecticides that act on particular pests while sparing beneficial insects. Electrophysiological studies on cultured Drosophila cholinergic neurons show partial agonist actions of the neonicotinoid imidacloprid and super-agonist actions of another neonicotinoid, clothianidin, on native nAChRs. Recombinant hybrid heteromeric nAChRs comprising Drosophila Dalpha2 and a vertebrate beta2 subunit have been instructive in mimicking such actions of imidacloprid and clothianidin. Unitary conductance measurements on native nAChRs indicate that more frequent openings of the largest conductance state may offer an explanation for the superagonist actions of clothianidin.